2022
DOI: 10.17678/beuscitech.1067376
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the contribution of the reinforcement tie to the seismic behavior of reinforced-concrete columns

Abstract: In reinforced-concrete structural columns, special earthquake reinforcement ties are used as well as longitudinal and transverse reinforcement. Deficiencies related to all these reinforcements can cause different levels of damage to the reinforced-concrete structural elements after the earthquake. Within the scope of this study, a total of eight different structural models were created for the reinforcement-ties effect in reinforced-concrete columns, considering four different reinforcement-tie models and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In order to obtain a comprehensive assessment of the seismic behavior of reinforced concrete structures, this study specifically focuses on the effect of two different types of stirrups, i.e., hooked and unhooked stirrups. Previous research has shown that hooked stirrups can improve energy dissipation and ductility by providing additional restraint to the concrete core, while unhooked stirrups, although widely used, may provide relatively limited benefits in this regard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Rosso et al [19] estimated the effect of corrosion on the capacity and ductility in their study.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a comprehensive assessment of the seismic behavior of reinforced concrete structures, this study specifically focuses on the effect of two different types of stirrups, i.e., hooked and unhooked stirrups. Previous research has shown that hooked stirrups can improve energy dissipation and ductility by providing additional restraint to the concrete core, while unhooked stirrups, although widely used, may provide relatively limited benefits in this regard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Rosso et al [19] estimated the effect of corrosion on the capacity and ductility in their study.…”
Section: Introductionmentioning
confidence: 99%